Pragmatic Violations of the Cooperative Principle in the Narrative of Prophet Ibrahim: Implications for Islamic Da'wah - Istiqomah, Salma Nur; Farisi, Mohamad Zaka Al; Supriadi, Rinaldi (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
This study aims to examine violations of Grice’s Cooperative Principle in the story of Prophet Ibrahim based on QS. Al-Anbiya: 51–70, and to explore its relevance to contemporary da'wah strategies. The focus of the research is directed at prophetic dialogues involving Ibrahim that contain maxim violations—quantity, quality, relevance, and manner—not merely as linguistic deviations but as rhetorical strategies to convey the message of monotheism persuasively and contextually. This study employs a qualitative-descriptive method with a pragmatic content analysis approach. Data were collected through documentation of Qur’anic verses containing dialogical narratives, particularly from Surah Al-Anbiya, and were analyzed based on the Cooperative Principle and Conversational Implicature theory developed by H. P. Grice. The findings reveal four key verses that strategically demonstrate maxim violations: QS 21:53 (relevance), QS 21:56 (quantity), QS 21:63 (quality), and QS 21:66 (manner). These violations do not hinder communication; rather, they serve as rhetorical devices to provoke the audience’s awareness of the irrationality of idol worship and the importance of monotheism. In conclusion, maxim violations in the story of Prophet Ibrahim reflect communicative wisdom in prophetic da'wah. This approach is relevant to modern da'wah contexts, as it shows that non-literal yet reflective and rhetorical communication strategies can enhance the effectiveness of Islamic preaching. This study offers a novel integration of pragmatic analysis and Qur’anic narrative interpretation, revealing how violations of the Cooperative Principle inform effective strategies for contemporary Islamic da'wah communication.